2018
DOI: 10.1159/000487477
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprogressive Disease in the Irradiation Field after a Single Dose of Nivolumab for Gastric Cancer: A Case Report

Abstract: Following the ATTRACTION-2 study, nivolumab was approved for advanced gastric cancer in Japan. However, pseudoprogression and hyperprogressive disease have been reported in patients treated with immune checkpoint inhibitors. We report a patient with gastric cancer who received nivolumab after radiotherapy only to experience rapid progression within the irradiation field after the first immunotherapy session. A 66-year-old man with dysphagia visited our hospital and was diagnosed with stage IV gastroesophageal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…Hyperprogression has so far been increasing described in a wide variety of cancers including lung cancers, head and neck cancers urothelial carcinoma, and melanomas [14-16]. While hyperprogression has been previously documented in GEJ tumors after nivolumab, to our knowledge there has not been reportage of HP in GEJ tumors after usage of pembrolizumab as we have described in our case [1].…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Hyperprogression has so far been increasing described in a wide variety of cancers including lung cancers, head and neck cancers urothelial carcinoma, and melanomas [14-16]. While hyperprogression has been previously documented in GEJ tumors after nivolumab, to our knowledge there has not been reportage of HP in GEJ tumors after usage of pembrolizumab as we have described in our case [1].…”
Section: Discussionsupporting
confidence: 47%
“…Even though hyperprogression is increasingly reported among other cancers, it is exceedingly rare among gastroesophageal junction (GEJ) tumors. The previously reported case in a GEJ tumor was in the setting of nivolumab use [1]. To our knowledge there has been no previously reported hyperprogression in GEJ tumors after pembrolizumab use and we present the first known occurrence of this in the case below.…”
Section: Introductionmentioning
confidence: 78%
“…However, the activities of immune checkpoint inhibitors (ICIs), are different from cytotoxic agents, and pseudoprogression and hyperprogressive disease have been reported in patients treated with ICIs. In gastric cancer, hyperprogressive disease has been previously reported [ 10 ]. When the pseudoprogression occurred, we considered a change in treatment according to RECIST because we could not decide whether the progression was pseudoprogression or hyperprogressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…The literature regarding therapeutic options for hyperprogression of patients is limited to case reports, although data regarding second progression‐free survival from randomized trials may shed more light on this question in the future. In some case reports, patients rapidly declined and died without any subsequent therapy . A case report detailing post‐pembrolizumab hyperprogression in an anorectal melanoma patient reported that the patient received one cycle of dacarbazine without clinical improvement .…”
Section: Discussionmentioning
confidence: 99%
“…In some case reports, patients rapidly declined and died without any subsequent therapy. 11,12 A case report detailing post-pembrolizumab hyperprogression in an anorectal melanoma patient reported that the patient received one cycle of dacarbazine without clinical improvement. 13 In fact, most of the studies thus far recommend avoiding future immunotherapy use altogether in this subgroup given the risks of hyperprogression.…”
Section: Discussionmentioning
confidence: 99%